2000
DOI: 10.1105/tpc.12.7.1031
|View full text |Cite
|
Sign up to set email alerts
|

A Unique 33-kD Cysteine Proteinase Accumulates in Response to Larval Feeding in Maize Genotypes Resistant to Fall Armyworm and Other Lepidoptera

Abstract: Plants respond to insect feeding with a number of defense mechanisms. Using maize genotypes derived from Antiquan germ plasm that are resistant to Lepidoptera, we have demonstrated that a unique 33-kD cysteine proteinase accumulates in the whorl in response to larval feeding. The abundance of the proteinase increased dramatically at the site of larval feeding after 1 hr of infestation and continued to accumulate for as long as 7 days. The 33-kD cysteine proteinase was most abundant in the yellow-green portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
151
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 48 publications
2
151
1
4
Order By: Relevance
“…Its potential application to plant protection against insects is being investigated, particularly against the sugarcane borer, D. saccharalis. In agreement with Pechan et al (2000), we have found that mir1 is highly expressed in sugarcane callus, although higher expression levels were observed in seeds, root transition zone, stem and plants infected with H. rubrisubalbicans and A. diazotroficans (Figure 2d). …”
Section: Multiple Insect-resistance Genes and Their Sugarcane Ortholosupporting
confidence: 88%
See 1 more Smart Citation
“…Its potential application to plant protection against insects is being investigated, particularly against the sugarcane borer, D. saccharalis. In agreement with Pechan et al (2000), we have found that mir1 is highly expressed in sugarcane callus, although higher expression levels were observed in seeds, root transition zone, stem and plants infected with H. rubrisubalbicans and A. diazotroficans (Figure 2d). …”
Section: Multiple Insect-resistance Genes and Their Sugarcane Ortholosupporting
confidence: 88%
“…Another interesting insect-resistance gene from a resistant inbred maize line has recently been isolated and characterized by Pechan et al (2000), the gene product being a 33-kDa cysteine proteinase (encoded by mir1 gene) which inhibits the growth of a wide range of lepidopteran larvae. Pechan et al suggest that this might be a novel insect defense mechanism in plants, although its mode of action is still unclear.…”
Section: Multiple Insect-resistance Genes and Their Sugarcane Ortholomentioning
confidence: 99%
“…The Z-FR-AMC substrate was used for kinetic profiling either at 0.25 mM or in a dilution series to determine kinetic constants. The catalytic competence of dionain-1 at different temperatures (4,20,30,40,50,60,70, and 80°C) was probed by end point fluorescence after 15-min incubation of dionain-1 in preheated 50 mM sodium acetate, pH 5.5, assay buffer containing 2 mM DTT and 0.25 mM Z-FR-AMC. The reaction was stopped by the addition of 1 mM E-64 and incubation for 10 min at room temperature before measuring total fluorescence.…”
Section: Mass Spectrometry Analyses (Lc-ms/ms)-mentioning
confidence: 99%
“…18 The maize genotype, Mp708, developed by classical plant breeding is remarkably resistant to different feeding styles of herbivore pests. 12,[19][20][21] Previous studies have shown that Mp708 provides resistance to caterpillars by rapidly accumulating Maize insect resistance1-Cysteine Protease (Mir1-CP), a papain-like protease. 19 Furthermore, it has been shown that Mir1-CP is localized in maize vascular tissues.…”
mentioning
confidence: 99%
“…12,[19][20][21] Previous studies have shown that Mp708 provides resistance to caterpillars by rapidly accumulating Maize insect resistance1-Cysteine Protease (Mir1-CP), a papain-like protease. 19 Furthermore, it has been shown that Mir1-CP is localized in maize vascular tissues. 22 Interestingly, Mir1-CP, a phloem-mobile protein, accumulates in roots in response to foliar feeding by FAW.…”
mentioning
confidence: 99%